Antifungal and Wound Healing Activities of Chitosan Nanoparticles from Green Mussel Shell (Perna viridis) and Jernang (Daemonorops draco) Ethanol Extract Dressing Patch - Novi Nuraeni; Arkhi Yuvie; Putu Pratama; Danisha Herianti; Valentina Kusumaningtyas; Jasmansyah Jasmansyah (Helium: Journal of Science and Applied Chemistry, 2022)
The development of chitosan nanoparticles and jernang (Daemonorops draco) as wound medicine materials have received a lot of attention from researchers. In this research the two materials will be combined. The antifungal of the materials determined based on inhibition test of Candida albicans and Malassezia furfur. The wound healing activities determined based on the in vivo wound healing test on Wistar rat (Rattus novergicus). The materials applicated on wound dressing patch. Chitosan was sinthesized from green mussels shell waste (Perna viridis L). The result showed that the yield of chitosan was 64.67% and degree of deacetylation (DD) was 69.53%. Meanwhile, chitosan nanoparticles can be prepared based on ball mill process. The result showed that average of the particles size was 437.6 nm (nanoparticles size is 1-1000 nm). Jernang was obtained by maseration process using ethanol organic solvents technical. The yield was 22.41% and showed positively of alkaloid, saponin, flavonoid and triterpenoid test. F3 has highest activies on antifungal and wound healing test results.Â